The Impact of Social Media Usability and Knowledge Collecting on the Quality of Knowledge Transfer: An Empirical Study among Saudi Context (Global Journal of Management and Business Research, 2017)
Abstract not found
Keywords: social media usability; knowledge management; knowledge transfer; knowledge sharing; knowledge collecting